Vascular Adhesion Protein-1 (VAP-1)/Semicarbazide-Sensitive Amine Oxidase (SSAO): A Potential Therapeutic Target for Atherosclerotic Cardiovascular Diseases - Li, Hui; Du, Shiyu; Niu, Panpan; Gu, Xiaosong; Wang, Jun; Zhao, Ying (Frontiers in Pharmacology, 2021)
Vascular adhesion protein-1 (VAP-1) is a semicarbazide-sensitive amine oxidase (SSAO), whose enzymatic activity regulates the adhesion/exudation of leukocytes in/from blood vessels. Due to its abundant expressions in vascular systems and prominent roles in inflammations, increasing attentions have been paid to the roles of VAP-1/SSAO in atherosclerosis, a chronic vascular inflammation that eventually drives clinical cardiovascular events. Clinical studies have demonstrated the potential values of soluble VAP-1 (sVAP-1) for diagnosis and prognosis of cardiovascular diseases. Recent findings revealed that VAP-1 is expressed in atherosclerotic plaques and treatment with VAP-1 inhibitors alleviates the progression of atherosclerosis. This review will focus on the importance of VAP-1/SSAO for the progression of atherosclerotic lesions and therapeutic potentials of VAP-1 inhibitors for cardiovascular diseases.